Brexit: past, present and future - Górriz López, Carlos (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The brexit is a historic milestone that deserves an accurate analysis as it is the first time that a Member State leaves the European Union. After the introduction (§ I), we explain the withdrawal process, remarking the problems raised by the application of article 50 TEU (§ II). Afterwards, we comment the principal questions of the Withdrawal Agreement (§ III), whose purpose is to solve the pending questions between the United Kingdom and the European Union. In the part IV we study the future of their relationship. On the one hand, the main consequences of the withdrawal. On the other, the options that existed to channel the relationship, the obstacles that have appeared during the negotiation and briefly the Commerce and Cooperation Agreement.